Exploring Personal Resources and Its Relationship with Work Engagement: A Systematic Review - Kelesoglu, Osman; Fontaine, Rodrigue Ancelot Harvey; Sharofiddin, Ashurov (Journal of Business Management and Accounting, 2024)
This systematic review of 55 empirical studies explores the relationship between personal resources and work engagement in various work environments. Its contribution is threefold: first, to identify the constructs that illustrate the ability of personal resources; second, to analyse current methods for studying personal resources and highlighting their limitations in theoretical generalisation; and third, to examine the role of personal resources to influence work engagement. The review identifies notable gaps in existing research and offers valuable perspectives to promote employee engagement in different professional settings. Findings highlight the need for cultural and sector-specific research to understand diverse responses to job demands and resources. It suggests the integration of emerging constructs like growth mindset and emotional intelligence into these models and emphasises the need for a more varied methodological approach, including longitudinal and qualitative studies. Additionally, it highlights the need to explore the impact of social, cultural, and technological factors in this relationship. An implication from this study is that organisations can improve job satisfaction, reduce turnover intentions, and enhance overall performance by creating a supportive environment that encourages personal resources. This can be achieved through offering training and development programmes, fostering a positive work culture, and ensuring a balance between job demands and resources.
Keywords: Systematic review; personal resources; work engagement; JD-R theory